Writing the Past: Le Roy Ladurie and the Voice of the New History - Philippe Carrard (Studies in 20th & 21st Century Literature, 1985)
Just as in fiction, discursive strategies in history can reveal the very nature of a project. The positivist historiography that prevailed in the late 19th and early 20th centuries regarded historical facts as givens. Accordingly, it held as its ideal of writing the objective text, that is. the text from which the historian's mediation would be carefully erased. The New History, on the other hand, considers all research to be grounded in a researcher and seeks to indicate by various means that the text does not generate itself. In Carnival in Romans, for example, Le Roy Ladurie explicitly resorts to various facets of the "I": that of the histor, going about the job of uncovering the evidence: that of the commentator, providing historical parallels and explanations; and even that of the emotional self (Barthes' personne passionnelle), making judgments on events and people in the narrative. These changes in writing conventions point to the emergence of a new historical paradigm. At the same time, they overturn the view of the historical text as a non-problematic vehicle for reporting "reality": this text, for the New Historians, becomes a construct, and is presented as such.
Keywords: late 19th; 20th; century; centuries; historical facts; objective text; New History; Carnival in Romans; Le Roy Ladurie; histor; " I" Barthes; personne passionnelle; reality; New Historian